Comparative studies on the proximate composition, mineral and anti-nutritional factors in the seeds and leaves of African Locust Bean (Parkia biglobosa) (2014)
The seeds and leaves of African Locust Bean (Parkia biglobosa) were evaluated for their proximate analysis, minerals and anti-nutritional factors. Atomic absorption spectrometry was used in the determination of the levels of Ca, Mg,K, Na, Mn, Fe, Cu and Zn. Anti-nutritional Factors (ANFs), including Trypsin inhibitor, oxalates, phytates, tannins, saponins, hydrocyanic acid were also determined using appropriate techniques. The result showed that the seeds of P.biglobosa had significantly higher (p<0.05)crude protein (33.50%), crude fat (49.20%) and %dry matter (95.20%) contents compared to the leaves having crude protein(18.40%), crude fat (8.11%) and %dry matter (88.80%), while the leaves had significantly higher (p<0.05) contents of ash (13.60%), crude fibre(18.90%) and moisture (11.20%) as against the seeds havingash (4.81%), crude fibre(4.66%)and moisture (4.89%). The mineral content of the analyzed samples showed that the seeds were richer in Ca (0.703%), Mg (0.356%), K (0.211%), Na (86.729ppm), Mn (54.811ppm), Fe (69.828ppm), Cu (9.766ppm) and Zn (12.156ppm), while the leaves recorded higher Phosphorus level (79.833ppm) than the seeds. For the ANFs, the seeds recorded higher levels of trypsin inhibitor (0.059+0.01), haemagglutinating units (46.00+0.07) and tannins (0.51+0.00) than the leaves, while the leaves recorded higher levels of oxalates (0.97+0.00), phytates (2.16+0.03), saponins (1.24+0.00) and hydrogen cyanide (87.9+0.56)than the seeds. The overall results are suggestive of higher nutritional quality of the seeds than the leaves due to higher mineral contents and lower presence of some anti-nutritional factors.